Predictive Marketing Regarding Brand Awareness of Gen Z: Brand Equity, Digital Media Content or Emotions Lead to Purchase? - Lutfije Ademi; Jusuf Zeqiri (ENTRENOVA - ENTerprise REsearch InNOVAtion, 2025)
This article investigates the effect of brand awareness, brand equity, digital media content and emotions on purchase intention of Gen Z. The scope of study is focused on people born in the period 1997 - 2012 or Gen Z in North Macedonia. The answers are retrieved from an online questionnaire, delivered to 444 responders. The data is analyzed using regression model. The findings show that all the independent variables, such as: brand equity, brand awareness, digital media content and emotions are positively related to the dependent variable, which is purchase intention. Thus, we concluded that brand awareness, brand equity, digital media content and emotions have a positive impact on purchase intention of Gen Z.
Keywords: J11; J13; 330; generation Z; brand equity; brand awareness; digital media content; emotions